Study of the clinical profile and etiology of neonatal seizures in a tertiary care centre of Bundelkhand region - Sodhi, Kartar S.; Gupta, Sapna; Kankane, Aradhana; Gautam, Rajni (International Journal of Contemporary Pediatrics, 2026)
Background: Neonatal seizures are among the most common neurological emergencies, contributing to significant morbidity and mortality. Their causes vary, including hypoxic-ischemic encephalopathy (HIE), infections, metabolic disorders, and intracranial hemorrhage. Seizures in neonates often result in long-term neurodevelopmental challenges, making early diagnosis and intervention crucial. This study aims to assess the prevalence, clinical presentation, etiological factors in neonatal seizures in a tertiary care center in the Bundelkhand region. Methods: This prospective observational study was conducted at the neonatal intensive care unit (NICU) of Maharani Laxmi Bai Medical College, Jhansi, Uttar Pradesh, from May 2023 to April 2024. A total of 140 neonates diagnosed with seizures and hospitalized for more than 24 hours were included. Data collection involved seizure type, onset, clinical and neurological assessments, and investigations such as electroencephalography (EEG), cranial ultrasound, and metabolic screening. Results: Among the 140 neonates, 69.3% were outborn, with HIE (65.7%) being the most common cause, followed by septicemia (20.7%) and metabolic disorders (5%). Multifocal clonic seizures (37.9%) were most frequent, followed by subtle seizures (34.3%). Conclusions: Neonatal seizures remain a major concern, with HIE being the leading cause. A significant proportion of affected neonates experience neurodevelopmental delays, emphasizing the need for early recognition, timely intervention, and long-term follow-up. The findings draw attention to Improved neonatal care and early intervention at the time of delivery in form of widespread neonatal resuscitation training program for all the health care staff who care for newborn at the time of delivery.